Problems and Solutions. Issue 2 (7th February 2022) - Ullman, Daniel H.; Velleman, Daniel J.; Wagon, Stan; West, Douglas B.; ,
Abstract : Proposed problems, solutions, and classics should be submitted online at americanmathematicalmonthly.submittable.com/submit . Proposed solutions to the problems below must be submitted by June 30, 2022. More detailed instructions are available online. Proposed problems must not be under consideration concurrently at any other journal nor be posted to the internet before the deadline date for solutions. An asterisk (*) after the number of a problem or a part of a problem indicates that no solution is currently available .